Economic and Financial Reform in Nicaragua: Challenges and Opportunities to 2025 - Sohn, Ira (Journal of Applied Business and Economics, 2017)
The paper reviews Nicaragua’s vital statistics and the major economic and political events since the end of the Somoza Era. The poorest country in Central America, Nicaragua is projecting a larger role in the global economy because of its plan to construct a canal to rival the Panama Canal, which would have major consequences for Nicaragua and Panama as well as for China and the United States. Using a framework that assesses the performance of a national economy that participates in today’s globalized world, I identify the strengths and weaknesses of Nicaragua towards the end of enhancing the future performance of its economy.